Community Participation in OBT Quality Assurance - Awakde, Bayamy Tchande (The Bible translator, 2025)
Though still a relatively new approach to Bible access, oral Bible translation (OBT) is already being practised by many Bible translation organisations. It serves both non-literate individuals and oral-culture communities—all those whose preferred modes of communication are audio and audiovisual. In the past, Bible translation agencies focussed almost entirely on written translation, failing to perceive the potential of oral translation for those who prefer this mode of communication. The current initiatives require a new range of competencies, including an understanding of OBT processes, of the context, of testing parameters, and of the discourse structure of the receptor language. A good understanding of the local context enables translators to identify individuals and groups who can best check the translation. And understanding the discourse structure of the receptor language enables them to ask the right checking questions. Community checking is essential for a natural and acceptable translation. We suggest some guidelines for community-based quality assurance (QA) of OBTs, and a case study illustrates the approach.